2012
DOI: 10.3174/ajnr.a3058
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility-Weighted Imaging: A New Tool in the Diagnosis and Evaluation of Abnormalities of the Vein of Galen in Children

Abstract: SUMMARY:We retrospectively identified 9 consecutive children, 3 males and 6 females (age 5.2 Ϯ 6.3 years, range 1 day to 18 years), with known or suspected AVGs who underwent MR imaging, including SWI, at our institution between January 2007 and March 2011. On the SWI sequence, arterialized blood flow was considered to be present in the vein of Galen or its tributaries when these showed abnormal signal hyperintensity from arteriovenous shunting. SWI findings were correlated with findings from DSA studies or fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…When dealing with children and especially critically ill newborns, better imaging modalities of the veins without the use of contrast material would be highly preferable and crucial. In this context, further research on SWI and VGM, as recently published by Jagadeesan et al14 is needed.…”
Section: Discussionmentioning
confidence: 99%
“…When dealing with children and especially critically ill newborns, better imaging modalities of the veins without the use of contrast material would be highly preferable and crucial. In this context, further research on SWI and VGM, as recently published by Jagadeesan et al14 is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in agreement with previous studies showing that SWI and ASL are 2 effective techniques to detect intracranial AVS. [8][9][10][11][12][13][14][15] Jagadeesan et al 10 demonstrated that SWI was 93% sensitive and 98% specific for the detection of AVS in patients with AVM. SWI was also found to accurately differentiate between high-flow and low-flow abnormalities of the vein of Galen in children.…”
Section: Discussionmentioning
confidence: 99%
“…Angioarchitecture was characterized using MRI based on the work of Geibprasert et al 5 and Jagadeesan et al 6. Choroidal type VGMs have small plexiform arteriovenous choroidal shunts that can have a nidus-like appearance on MR images (see illustrative case No 1, figure 2).…”
Section: Methodsmentioning
confidence: 99%